Changes in potential denitrification-derived N2O emissions following conversion of grain to greenhouse vegetable cropping systems - Cao, J.; Lee, Juhwan; Six, J.; Yan, Y.; Zhang, F.; Fan, M. (2015)
© 2015 Elsevier Masson SAS. In China, considerable cropland previously under grain production has been rapidly converted to greenhouse vegetable production by farmers since 1980s. Vegetable crops generally require higher nitrogen (N) inputs from manure amendments and more frequent tillage and irrigation operations compared to grain crops. Here, we compared potential denitrification-derived N2O emissions across the soil profile (0-90cm depth) between grain and greenhouse vegetable fields. Denitrification enzyme activity (DEA) was assessed in the top 0-15cm soil layer. Soil samples from five wheat (Triticum aestivum L.) - maize (Zea mays L.) fields, paired with adjacent vegetable greenhouse fields, were collected across typical vegetable production regions. Conversion from the grain fields to the greenhouse vegetable fields led to greater potential denitrification-derived N2O emissions in the 0-15 and 15-30cm depths, respectively, with 4 and 3 times higher cumulative emissions over the 10-day incubation. Continuous manure amendments and chemical N input increased water extractable organic carbon and nitrate concentrations, which significantly enhanced potential denitrification-derived N2O production in the 0-30cm soil depth of vegetable crop fields. The differences in microbial community for the two cropping systems did not seem to affect the surface N2O production potential since denitrification enzyme activity were not significantly different between the two production systems. There was a small to negligible potential N2O flux in 30-90cm soil depths for both production systems because of limited carbon availability and microbial activity. Managing surface labile carbon and mineral N pool may be critical in reducing regional N2O emissions in China's greenhouse vegetable production systems.